Female sexual dysfunction in patients with psoriasis and vitiligo: an Egyptian pilot study - Hesham N Khaled; Eman A El-Sabagh; Heba A.S.K Bazid (Wolters Kluwer Medknow Publications, 2021)
Introduction Female sexual dysfunction (FSD) refers to a problem that occurs during the sexual response cycle that prevents the female from experiencing satisfaction from sexual activity. It is a multifactorial condition established in biological, psychosexual, and interpersonal factors. It is divided into four groups: sexual desire, arousal, orgasmic, and pain disorders. Psoriasis and vitiligo although being of different pathogenesis and clinical presentation, both of them are common chronic skin diseases associated with significant disfigurement and systemic comorbidities like cardiovascular disease in psoriasis and endocrinal diseases like diabetes mellitus and thyroid disorders in vitiligo. They can affect sexuality through both psychological and biological factors. Objective To evaluate the effect of psoriasis and vitiligo on female sexual function in a sample of Egyptian patients in a hospital-based study. Patients and methods This study included 150 participants: 50 psoriatic women, 50 women with vitiligo, and 50 age-, sociocultural level (degree of education, occupation, religion, and residence)-, BMI-, and marital history-matched normal women as a control group. Sexual activity was estimated by using an Arabic translation of the female sexual function index questionnaire. Results This study revealed that FSD in psoriasis and vitiligo female groups was higher than that in the control group (with P=0.027 and 0.005, respectively). There was no significant difference regarding sexual dysfunction in cases with associated comorbidities and cases with only psoriasis or vitiligo. Among psoriasis group, FSD was significantly associated with older age (P=0.017), progressive course (P=0.008), long disease duration (P=0.013), and psoriasis severity as assessed by psoriasis area and severity index (P<0.001). Among vitiligo group, FSD was significantly associated with the duration of marriage (P=0.023), progressive course (P=0.001), genital affection (P=0.015), acrofacial type (P=0.011), vitiligo severity as assessed by vitiligo area and severity index (P=0.01), and vitiligo activity as assessed by vitiligo disease activity score (P=0.015). Conclusion The authors concluded that the psychological burden of psoriasis and vitiligo can adversely affect sexuality.